Integration of Four Learning Theories to Increase Student Activeness in SKI Learning at Madrasah Tsanawiyah - Eva Marpuah; Maulida Fithria; Saidatul Fitri Rif'adina; Azkia El Insyira Averus; Lia Wantri Pegy Marlangen (Universitas Wahid Hasyim Semarang, 2025)
Learning the history of Islamic culture is often connoted with monotonous and rote learning, whereas this learning can actually also be used to develop attitudes and skills. This study aims to examine the integration of four learning theories to improve student creativity. This study is a qualitative study with a case study approach. Data collection techniques are carried out with documentation, observation and interviews with objects and subjects of research. Data analysis is carried out by; collecting data, grouping, categorizing, finding appropriate themes, and interpreting. The results of the study indicate that the integration of four learning theories in learning the history of Islamic culture is carried out according to the needs and suitability of learning objectives in each discussion theme. So that this integration is designed based on three categories of learning objectives, namely: cognitive, affective and psychomotor. So that this integration has significantly been able to increase students' cognitive, affective and psychomotor competencies. Therefore, this study can have an impact on the development of interesting Islamic cultural history learning and is able to increase student activity. Keywords: Four Theories of Learning, Integration, Activeness, Learning, SKI.